Blood orange juice intake changes specific bacteria of gut microbiota associated with cardiometabolic biomarkers - Corrêa, Telma Angelina Faraldo; Tobaruela, Eric de Castro; Capetini, Vinicius Cooper; Quintanilha, Bruna Jardim; Cortez, Ramon Vitor; Taddei, Carla R.; Hassimotto, Neuza Mariko Aymoto; Hoffmann, Christian; Rogero, Marcelo Macedo; Lajolo, Franco Maria (Frontiers in Microbiology, 2023)
Blood orange juice is an important source of flavanones and anthocyanins, mainly hesperidin, narirutin, and cyanidin-3-O-glucoside. The benefits of these bioactive compounds have been reported, but the mechanistic details behind their biological effects are not well established. This study investigated the effects of Moro orange (Citrus sinensis L. Osbeck) juice (MOJ) on gut microbiota composition and cardiometabolic biomarkers in overweight women. In this study, twelve overweight women (BMI from 25.0 to 29.9 kg/m2), aged 18–37 years, consumed 500 mL of MOJ every day for 4 weeks. We assessed the gut microbiota composition, levels of short-chain fatty acids (SCFAs), cardiometabolic biomarkers, and insulin resistance (HOMA-IR) at baseline and after 2 weeks and 4 weeks of MOJ intake. The results suggested that MOJ intake affected the abundance of specific operational taxonomic units (OTUs) of the gut microbiota but did not significantly alter the diversity and general composition of the gut microbiota. However, MOJ intake increased the production of SCFAs, especially propionic and isobutyric acids, and significantly improved cardiometabolic biomarkers such as blood pressure and plasma VCAM-1 levels in the overweight women. Additionally, we observed significant associations between gut microbiota OTUs belonging to the Bacteroidetes phyla and Prevotella 9 genera and the cardiometabolic biomarkers. Furthermore, MOJ reduced fasting glucose and insulin levels and HOMA-IR values, thereby enhancing insulin sensitivity in the insulin-resistant overweight women. Finally, we highlighted the importance of orange juice intake duration because some beneficial changes such as blood pressure improvements were evident at the 2-week time interval of the intervention, but other changes became significant only at the 4-week interval of MOJ intake. In conclusion, our study demonstrated that changes in specific OTUs of the gut microbiota in response to MOJ intake were associated with significant improvements in some cardiometabolic biomarkers and SCFA levels in overweight women with insulin resistance.